Influence Of Learning Methods And Learning Motivation On The Learning Outcomes Of Service In Volleyball - Tomasoa, Yellia (JUARA : Jurnal Olahraga, 2024)
Abstract ___________________________________________________________This study aims to analyse: (1) the difference in the effect of STAD and TGT learning methods on learning outcomes of service in volleyball games, (2) the interaction between learning methods and motivation on learning outcomes of service in volleyball games, and (3) the difference in the effect of high motivation trained with STAD method and TGT method on learning outcomes of service in volleyball games, (4) the difference in the effect of low motivation trained with STAD method and TGT method on learning outcomes of service in volleyball games, This experimental research uses a treatmen by level 2 x 2 design. The subjects in this study were 24 Xaverius High School students. Data analysis technique using ANOVA. Based on hypothesis testing, the results of this study are: (1) overall there is a real difference between STAD and TGT methods on the learning outcomes of service in volleyball games. With the results of analysis of variance at the level of significance α = 0.05 obtained Fhitung = 21.48 and Ftabel = 4.06 so that Fhitung > Ftabel , (2) there is an interaction between the learning methods used with motivation to the learning outcomes of service in volleyball games. With the calculation of anava, that the price of Fhitung interaction F(AxB) = 14.97 and Ftabel = 4.06 so that Fhitung > Ftabel , (3) There are differences in learning outcomes service in groups of students who have high motivation trained with STAD method and TGT training method (Qhitung 6.74 > 3.86 Q ,). 3.86 Qtabel ,), (4) There is no difference in service learning outcomes in groups of highly motivated students trained with the STAD method and the TGT training method (Qcount 1.00 < 3.79 Qtabel) . Conclusion: (1) STAD method is better than TGT method on the learning outcomes of service in volleyball game, (2) there is an interaction between learning methods and concentration on the learning outcomes of service in volleyball game, (3) students with high motivation and trained with STAD and TGT methods are better than students with low motivation trained with STAD and TGT methods.